Pembelajaran Inquiry Terbimbing dengan Metode Eksperimen untuk Meningkatkan Motivasi dan Prestasi Belajar Biologi Siswa SMA - Darmiyati, Endang Sri (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2020)
This study aims to explore (1) whether through Guided Inquiry Learning with the Experiment Method can improve learning motivation for XI grade students; (2) whether through Guided Inquiry Learning with Experiment method can improve learning achievement for XI grade students.This study follows a class action research procedure that starts from the planning process, implementation of the action, observation and ends with a process of reflection on the results of the action. The research data was collected through test techniques. The test technique is used to collect data on students' abilities.The research findings show that Guided Inquiry Learning with Experiment method can significantly increase motivation and learning achievement Biology Basic Competency Test of Food from the initial condition of low motivation to change into a highly motivated final condition. This method is also able to improve student learning achievement. This is indicated by changes in the average score in the first cycle 69.5 and 84.9 in the second cycle; the average completeness in the first cycle was 34.3% and the average completeness in the second cycle was 96%. Thus Guided Inquiry Learning with Experimentation methods can improve motivation and learning achievement Biology Basic Competence of Food Tests on Students.